Know Before You Ship : Raising Awareness of Dangerous Goods Classification Through University Community Service in Manila - Devi Marlita; Juliater Simarmata; Sarinah Sihombing; Euis Saribanon; Sri Handayani; Nursery Alfaridi Nasution (Asosiasi Periset Bahasa Sastra Indonesia, 2025)
As shipping activities through various modes of transportation increase, the need for adequate understanding of dangerous goods is becoming increasingly important, especially among the younger generation. Unfortunately, many students still do not understand the classification and risks associated with transporting these goods. This community service activity aims to increase awareness and understanding of high school students in the Philippines regarding the classification of dangerous goods and the importance of safety in the shipping process. The activity was carried out through an interactive outreach method that included visual presentations, case studies, and simple simulations to make the material easier to understand and apply. The material provided refers to international standards, namely the International Maritime Dangerous Goods (IMDG) Code and ICAO Technical Instructions (ICAO-TI), which are important references in the classification and handling of dangerous goods globally. Evaluation was carried out through pre-tests and post-tests to measure the level of student understanding before and after the activity. The results showed a significant increase in students' ability to recognize symbols, types of dangerous goods, and initial actions to be taken when faced with these goods. These findings confirm that the right educational approach can increase early awareness among students as potential actors in the logistics chain. It is hoped that similar programs can be implemented widely and sustainably in various educational institutions to minimize the risk of sending dangerous goods due to a lack of public knowledge.